Calix(4)pyrrolato aluminate catalyzes the dehydrocoupling of phenylphosphine borane to high molar weight polymers - Schön, Florian; Sigmund, Lukas M.; Schneider, Friederike; Hartmann, Deborah; Wiebe, Matthew A.; Manners, Ian; Greb, Lutz (Angewandte Chemie. International edition, 2022)
High molar weight polyphosphinoboranes represent materials with auspicious properties, but their preparation requires transition metal-based catalysts. Here, calix[4]pyrrolato aluminate is shown to induce the dehydropolymerization of phosphine boranes to high molar mass polyphosphinoboranes (up to Mn=43 000 Da). Combined GPC and 31P DOSY NMR spectroscopic analyses, quantum chemical computations, and stoichiometric reactions disclose a P−H bond activation by the cooperative action of the square-planar aluminate and the electron-rich ligand framework. This first transition metal-free catalyst for P−B dehydrocoupling overcomes the problem of residual d-block metal impurities in the resulting polymers that might interfere with the reproducibility of the properties for this emerging class of inorganic materials.
Im Titel steht 4 in eckiger Klammer
Version of record online: March 29, 2022
Gesehen am 04.10.2022